Intensive English Language Programme: A Needs Assessment - Sarudin, Isarji; Siddiq, Nikhat; Mohd Noor, Zainab (IDOSI Publication, 2013)
Abstract: Conducting needs assessment for language programmes is important to gain understanding of the needs of the learners, to document programme effectiveness in terms of the objectives and outcomes being met,to examine strengths and weaknesses and to provide empirical evidence of the merit and worth of the programme. The main objective of this paper is to report the findings of a study to investigate the needs of students in the Intensive English Language Programme at the International Islamic University Malaysia. The quantitative study employed survey questionnaires distributed to 30 students and 8 teachers. The findings of the study indicate thatboth students and instructors expressed that all English language sub -skills taught in the programme were either useful or more useful to students. The findings of the study, based on the Mann-Whitney U tests, also reveal that both the students and instructors shared similar views in terms of students’ English language needs in the intensive English language programme.